Evaluation of FDM Pattern with ABS and PLA Material - Hafsa, M.N.; Ibrahim, M.; Wahab, M. S.; Zahid, M.S. (2023)
Selection of the most suitable Rapid Prototyping (RP) and manufacturing process for a specific part creation is a difficult task due to the development of RP processes and materials. Most current RP processes can build with more than one type of material. The paper presents the evaluation on Acrylonitrile Butadiene Styrene (ABS) and Polylactic acid (PLA) part produced from Fused Deposition Modeling (FDM) as a master pattern for Investment Casting (IC) process. The main purpose of this research is to evaluate the dimensional accuracy and surface roughness for hollow and solid part of FDM pattern for IC process with different layer thickness. The value were taken for both before and after the casting process. Results show that model fabricated with hollow internal pattern structure (ABS material) that produced by low layer thickness is better than other models in terms of its dimensional accuracy (-0.19666mm) and surface roughness (1.41μm). Even though the ABS built part performed better as the model, the PLA build part produces better overall casting result. Final part fabricated with solid pattern (PLA material) that produced by high layer thickness is better than other final parts which its dimensional accuracy (-0.12777mm) and surface roughness (3.07μm)